EFFECT THE UNDERSTANDING OF TAXATION, TAX SANCTIONS AND TAXPAYER AWARENESS OF TAXPAYER COMPLIANCE (RESEARCH ON TAXPAYERS OF INDIVIDUAL ENTREPRENEURS IN TANGERANG REGION) - Triandani, Megi; Apollo, Apollo (Dinasti International Journal of Digital Business Management, 2020)
The purpose of this research are to examine how much influence the understanding of taxation, tax sanctions and taxpayer awareness of tax compliance. The population in this research are the taxpayers of individual entrepreneurs in the Tangerang Region, then the samples are drawn using a method simple random sampling. Using quantitative and analytic statistics method for the analytical method that are multiple linear regression analysis method. The results showed that taxpayer understanding and taxpayer awareness affected taxpayer compliance while tax sanctions did not affect the compliance of taxpayers of individual entrepreneurs in the Tangerang Region. The data analysis technique used in this research was SPSS v.23